ZPD Technological Learning Environment In Learning Computational Thinking Skill-Based Mathematics - Kamid, Kamid; Sutrisno, Sutrisno; Kurniawan, Dwi Agus; Anwar, Khairul; Triani, Elza; Septi, Sabila Eka (Jurnal Pedagogi dan Pembelajaran, 2023)
This research was conducted as an innovation related to learning problems that often occur in students. This research aims to develop a technological prototype of the mathematics-computation learning environment for playing skills using the Zone of Proximal Development (ZPD) approach based on intelligent technology. This type of research is Research and Development using the 4-D model flow (Four-D Models). The sampling technique is purposive sampling. Data collection in this study uses angles for learning environment data sources and computational thinking. Then interviews are used as a source of learning experience data. Data analysis on quantitative data types used descriptive and inferential statistics in the form of independent sample t-tests and the Miles and Huberman model. This study found differences in the computational thinking abilities of male and female students, and the dominant computational thinking abilities were male students. This development research has produced an online learning environment product where the product is valid in the opinion of experts in the good category, exciting and feasible to implement. The learning environment assists and facilitates students in learning mathematics by using technology geared toward improving thinking.